Information barriers and SRI market participation: Can sustainability and transparency labels help? - Gunnar Gutsche; Bernhard Zwergel (Philipps-University Marburg, School of Business and Economics, 2016)
This study empirically analyzes barriers preventing private investors from participating in the market of sustainable and responsible investments (SRI). Thereby, we link the strand of literature regarding participation costs of stockholding, i.e. information and transaction costs, to SRI market participation. The empirical analysis is based on a large online representative dataset for German financial decision makers containing data from a survey and a stated preferences discrete choice experiment, which refers to investment decisions between mutual funds. Contrary to most previous studies, we do not only differentiate between investors who are currently invested in SRI and those who are not invested. Instead we differentiate between four different investor groups, namely socially responsible, skeptical, interested, and conventional investors. We find that these groups face different barriers regarding SRI market participation. Particularly too high (perceived) information costs regarding SRI are a reason for private investors not to invest (more) in SRI. Having not received an offer by their bank seems to be a big hurdle especially for interested investors who seem to have problems overcoming the market entry barrier. Distrusting providers of SRI is an additional issue that especially hinders skeptical and conventional investors to invest (more) in SRI. Based on the experimental results, we see that information related barriers can be decreased by means of sustainability and/or transparency labels. Investor of all four groups have positive stated preferences for funds with transparency or sustainability labels. Hence, labels are an opportunity to decrease information costs of private investors and thus enhance individual demand for SRI.
Keywords: Q56; G11; M14; C25; 330; sustainable and responsible investments; microeconometric analysis; stated preferences; discrete choice experiment; sustainability label; transparency; distrust; participation costs; market participation